2008
DOI: 10.1016/j.vaccine.2008.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Addition of CpG ODN to recombinant Pseudomonas aeruginosa ExoProtein A conjugates of AMA1 and Pfs25 greatly increases the number of responders

Abstract: Both the blood stage protein apical membrane antigen 1 (AMA1) and the 25 kDa sexual stage protein (Pfs25) of Plasmodium falciparum are two leading candidates in malarial vaccine development. We have previously demonstrated that conjugation of these malarial antigens to recombinant Pseudomonas aeruginosa ExoProtein A (rEPA) significantly increased the mean specific functional antibody responses in mice; however, some mice responded poorly and were unable to demonstrate a functional response. We hypothesized tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 23 publications
1
19
0
1
Order By: Relevance
“…A phase 1 study demonstrated that human antibodies raised against a recombinant Pfs25 (Pfs25H) protein formulated in Montanide ISA 51, a water-in-oil adjuvant formulation, were biologically active in an ex vivo feeding assay (3), however, this formulation was not deemed suitable for a public health vaccine. More recently, in preclinical studies, Pfs25H has been shown to have enhanced immunogenic properties when chemically conjugated to a carrier molecule such as Neisseria meningitis outer membrane protein complex (4), or Pseudomonas aeruginosa ExoProtein A (EPA) (5,6). In particular, the chemically conjugated Pfs25-EPA has the biophysical features of a nanoparticle with a diameter of about 25 m in solution, similar in size to that of the RTS,S (7).…”
mentioning
confidence: 99%
“…A phase 1 study demonstrated that human antibodies raised against a recombinant Pfs25 (Pfs25H) protein formulated in Montanide ISA 51, a water-in-oil adjuvant formulation, were biologically active in an ex vivo feeding assay (3), however, this formulation was not deemed suitable for a public health vaccine. More recently, in preclinical studies, Pfs25H has been shown to have enhanced immunogenic properties when chemically conjugated to a carrier molecule such as Neisseria meningitis outer membrane protein complex (4), or Pseudomonas aeruginosa ExoProtein A (EPA) (5,6). In particular, the chemically conjugated Pfs25-EPA has the biophysical features of a nanoparticle with a diameter of about 25 m in solution, similar in size to that of the RTS,S (7).…”
mentioning
confidence: 99%
“…Surprisingly, despite adjuvant refinement of ML0276-based vaccines to generate a potent and transferable Th1 response, vaccination with ML0276 did not limit bacterial growth in the long-term footpad model. Due to its documented ability to induce potent Th1 responses against even weak antigens, we initially used CpG, a TLR9 agonist, to potentiate the response against ML0276 (10,48). The adjuvant properties of CpG have been well characterized for a variety of species, and various CpG DNAs are being used in human clinical trials (8,10,30,35,60,61).…”
Section: Resultsmentioning
confidence: 99%
“…32 Furthermore, chemical conjugation of PpPfs25H-A to either ExoProtein A (EPA) of Pseudomonas aeruginosa or an outer membrane protein complex of Neisseria meningitides was shown to have a dramatically enhancing effect on both anti-Pfs25 and TB antibody responses. [13][14][15][16] Chemically conjugated Pfs25-EPA nanoparticles were subsequently manufactured under current Good Manufacturing Practices conditions and evaluated in mice in the presence of Alhydrogel, demonstrating superior immunogenicity compared with unconjugated Pfs25 plus Alhydrogel. 33 A Phase 1 clinical trial (NCT01434381) in which 30 healthy malaria-naïve adult subjects received up to three doses of the Pfs25-EPA TBV candidate (8 or 16 µg of Pfs25 at 0 and 2 mo or 47 µg of Pfs25 at 0, 2, and 4 mo) has recently been completed.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these challenges, recent success has been achieved with recombinant versions of Pfs25 produced in yeast. [10][11][12][13][14][15][16][17] During the last two decades, several groups have demonstrated the potential of plants as an effective and highly scalable platform for production of recombinant vaccine antigens and therapeutic proteins (for a review see refs. 18 and 19).…”
Section: Introductionmentioning
confidence: 99%